Enhancement of Lodging Resistance and Lignin Content by Application of Organic Carbon and Silicon Fertilization in Brassica napus L. - Hu, Yue; Javed, Hafiz Hassan; Asghar, Muhammad Ahsan; Peng, Xiao; Brestic, Marian; Skalický, Milan; Ghafoor, Abu Zar; Cheema, Hafsa Nazir; Zhang, Fang-Fang; Wu, Yong-Cheng (Frontiers in Plant Science, 2022)
This study was aimed to investigate the effects of organic carbon and silicon fertilizers on the lodging resistance, yield and economic performance of rapeseed. Two cultivars: Jayou (lodging-resistant) and Chuannongyou (lodging-susceptible) were selected to evaluate the effects of various fertilizer treatments on rapeseed culm morphology, lignin accumulation, and their relationships with their lodging resistance indices. The results showed that both organic carbon and silicon fertilizer applications increased the plant height, basal stem diameter, internode plumpness and bending strength of rapeseed in both the studied years. The bending strength was significantly and positively correlated with the lodging resistance index and lignin content. It was found that both organic carbon and silicon fertilizers had improved the activities of lignin biosynthesis enzymes (PAL, 4CL, CAD and POD) and their related genes to increase lignin accumulation in the culm which ultimately improved the lodging resistance. At the same time, the thickness of stem cortex, vascular bundle area and xylem area were increased, and the stem strength was improved. The effect of silicon fertilizer was better than that of organic carbon fertilizer, but there was no significant difference with the mixed application of silicon fertilizer and organic carbon fertilizer. Similarly, silicon fertilizer increased the number of pods, significantly increased the yield and improved the economic benefit, while organic carbon fertilizer had no significant effect on the yield. Therefore, we believe that organic carbon and silicon fertilizer can improve the lodging resistance of rape stem by improving lignin accumulation and mechanical tissue structure, but the effect of silicon fertilizer is the best. Considering the economic benefits, adding silicon fertilizer can obtain more net income than the mixed application of silicon fertilizer and organic carbon fertilizer.